The THE RELATIONSHIP BETWEEN PERCEIVED SOCIAL SUPPORT AND CREATIVE THINKING SKILLS IN NURSING STUDENTS: Effect of Perceived Social Support Level on Creative Thinking Skills - DEMIR BARUTCU, Canan (Göbeklitepe Medical Science Journal, 2024)
This study was conducted in order to examine the relationship between perceived social support and creative thinking skills in nursing students. The descriptive and corelational study was carried out with 306 nursing students. Data were collected using a multidimensional scale of perceived social support and a creative thinking skills scale. The average perceived social support score of the students was the highest in the second year, and lowest in the fourth year. No significant difference was determined in the average score obtained from the creative thinking skill scale according to the grade level, and because the average score of all classes was between 40-64 points, all the students were classified as "above average level of creativity". The highest average scores were seen in fourth-grade students. There was no statistically significant relationship between the multidimensional perceived social support scale total score, sub-dimension scores, and creative thinking skills scale mean scores of the nursing students (p˃0.05). These results can be considered important in terms of showing the positive effect of nursing education on creativity, as the students were seen to be classified as above-average creativity and their creativity levels increased with increasing education.